Pengolahan Jeruk Siam dan Nanas menjadi produk bernilai jual tinggi di Desa Pulau Jambu, Kampar - Emma Riftyan; Yusmarini Yusmarini; Vonny Setiaries Johan; Shanti Fitriani; Edo Saputra; Yossie Kharisma Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The potential of Pulau Jambu in the agricultural aspect, especially Siamese oranges, is a potential in itself. The majority of the work of people in Pulau Jambu, Kuok District as Siamese orange farmers and the abundance of Siamese oranges in Pulau Jambu are one of the reasons for the purpose of this community service. The problem faced by Siamese orange farmers is they have lack of knowledge and skills in processing Siamese oranges so that the harvested Siamese oranges so far are only sold in fresh, not in processed. The method implemented in this community service activity is by providing guidance and training from the production aspect and the business management aspect. The training provided is processing Siamese oranges in the form of jam and drinks with the addition of pineapple which is also a local potential of Kampar Regency.